Strategi Digital Marketing Terhadap Kinerja Perguruan Tinggi - Elisabeth; Friska Wowiling (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2020)
The problems being faced by the University of Atma Jaya Makassar is a system of marketing, University of Atma Jaya Makassar did not go well, resulting in a decrease of the number of prospective students each year. This study aims to model the marketing system and help the marketing division in the use of the right marketing strategy used by the University of Atma Jaya Makassar. The method used in analyzing the problems that are happening in the marketing division, namely using the method of the analysis of SWOT to know where lies the strength, weakness, opportunity and threat, and the method of analysis of STP used to determine the map segmentation marketing, target marketing and position of the Universitas Atma Jaya Makassar in the share market in South Sulawesi.